Functional Implications of the Subcellular Localization of Ethylene-Induced Chitinase and [beta]-1,3-Glucanase in Bean Leaves. - Mauch, F. (1989)
Plants respond to an attack by potentially pathogenic organisms and to the plant stress hormone ethylene with an increased synthesis of hydrolases such as chitinase and [beta]-1,3-glucanase. We have studied the subcellular localization of these two enzymes in ethylene-treated bean leaves by immunogold cytochemistry and by biochemical fractionation techniques. Our micrographs indicate that chitinase and [beta]-1,3-glucanase accumulate in the vacuole of ethylene-treated leaf cells. Within the vacuole label was found predominantly over ethylene-induced electron dense protein aggregates. A second, minor site of accumulation of [beta]-1,3-glucanase was the cell wall, where label was present nearly exclusively over the middle lamella surrounding intercellular air spaces. Both kinds of antibodies labeled Golgi cisternae of ethylene-treated tissue, suggesting that the newly synthesized chitinase and [beta]-1,3-glucanase are processed in the Golgi apparatus. Biochemical fractionation studies confirmed the accumulation in high concentrations of both chitinase and [beta]-1,3-glucanase in isolated vacuoles, and demonstrated that only [beta]-1,3-glucanase, but not chitinase, was present in intercellular washing fluids collected from ethylene-treated leaves. Based on these results and earlier studies, we propose a model in which the vacuole-localized chitinase and [beta]-1,3-glucanase are used as a last line of defense to be released when the attacked host cells lyse. The cell wall-localized [beta]-1,3-glucanase, on the other hand, would be involved in recognition processes, releasing defense activating signaling molecules from the walls of invading pathogens.